What qualities are required for globally-relevant health service managers? An exploratory analysis of health systems internationally - Reema Harrison; Lois Meyer; Ashfaq Chauhan; Maria Agaliotis (BMC, 2019)
Abstract Background Globally, health service leaders and managers have a critical role in strengthening health systems. Competency frameworks for health service managers are usually designed to describe expectations of good performance of a health manager within a country-specific health sector context. However, a growing number of health service management roles operate beyond a country-specific level, with managers requiring a global perspective and the skills and knowledge to work effectively across a range of countries and contexts. This study provides an exploratory analysis of the most relevant qualities perceived to facilitate health service managers to be effective when working in such roles. Methods A qualitative, descriptive, and exploratory multi-centre study was undertaken. Semi-structured individual interviews were conducted between August and November 2017 with 15 health service managers or leaders at a range of levels from seven countries [Australia (5), China (2), Indonesia (3), Oman (1), Papua New Guinea (1), United Kingdom (1) and United States of America (2)]. Results Five themes emerged relating to the qualities required from health leaders in order to be effective when working in a global context: i) Managing and Making Change, ii) Collaborative Managers and Compassionate Leaders, iii) Continuous Learning, iv) Balancing Management Theory and Practice, and v) Leadership Skills. Conclusion Our findings highlight underpinning themes relating to making and managing change and collaboration, reflecting the changing needs of health services to deliver high quality care. These themes were identified in addition to some of the common qualities required of healthcare leaders and managers that are identified that reflect many country-specific frameworks.